In vitro and in vivo activity of liposome‐encapsulated curcumin for naturally occurring canine cancers. (8th August 2018) - Withers, Sita S.; York, Daniel; Johnson, Eric; Al‐Nadaf, Sami; Skorupski, Katherine A.; Rodriguez, Carlos O.; Burton, Jenna H.; Guerrero, Teri; Sein, Kriste; Wittenburg, Luke; Rebhun, Robert B.
Abstract : Curcumin has well‐established anti‐cancer properties in vitro, however, its therapeutic potential has been hindered by its poor bioavailability. Lipocurc is a proprietary liposome‐encapsulated curcumin formulation that enables intravenous delivery and has been shown to reach its highest concentration within lung tissue. The goal of this study was to characterize the anti‐cancer and anti‐angiogenic activity of Lipocurc in vitro, in addition to evaluating Lipocurc infusions in dogs with naturally occurring cancer. We therefore evaluated the effect of Lipocurc, relative to free curcumin, on the viability of canine osteosarcoma, melanoma and mammary carcinoma cell lines, as well as the ability of Lipocurc to inhibit endothelial cell viability, migration and tube formation. We also undertook a pilot clinical trial consisting of four weekly 8‐hour Lipocurc infusions in 10 cancer‐bearing dogs. Tumour cell proliferation was inhibited by curcumin at concentrations exceeding those achievable in the lung tissue of dogs. Similarly, equivalent high concentrations of Lipocurc and curcumin also inhibited endothelial cell viability, migration and tube formation. Four out of six dogs completing planned infusions of Lipocurc experienced stable disease; however, no radiographic responses were detected.